A Comparative Study Between The Use Of Scaffolding Technique And Write Pair Square (Wps) Technique In Increasing Students’ Descriptive Text Writing Ability - Pradana, Satria Adi; Pakas, Siti Zahra; Kurniawati, Dewi (English Education: Jurnal Tadris Bahasa Inggris, 2019)
The aim of this research is to investigate whether is there any significant differences of the achievements in writing descriptive text of students which one is better teaching by using Scaffolding Technique and Write Pair Square (WPS) Technique. This research was Statistic Group Comparison that used Simple Random Sampling. There were two groups that were given different treatment. The first group was the experimental class 1 as VIII C that was taught by using Scaffolding Technique, and the second group was the experimental class 2 as VIII B that was taught by using Write Pair Square (WPS) Technique. The result of data analysis showed that the result of T-test is 3.628 and the result of T-critical is 2.056, because the T-observed > T-critical. It means that there was a significant different achievement between the students those which one was better after teaching by using WPS and those which one was better after teaching by using Scaffolding toward students’ descriptive text writing ability